Implementation of IoT based smart street light intensity control system using IR and LDR sensors - Debata, Suchismita; Mantoliya, Rupa; Sahithi, Veena; Ratnam Kolluru, Venkata (International Journal of Engineering and Technology, 2018)
This research article gives an idea about advancements in energy saving of street lights and to reduce the power consumption. The pro-gramming terminology for building up the product to the Arduino board at long last, the framework has been effectively outlined and executed. Mainly using two sensor IR and LDR sensor to implement intensity control of street light.IR sensor is use to detect the motion of the objects and LDR (light dependent resistor) used to recognize day-evening. When light falls on the LDR depending on resistance of light the intensity of light is decreased or increase. The street light is automatically ON in evening 6pm and OFF till morning. Through mobile app also we can operate the street light. Using Arduino board for implementing the intensity control of street light.